The theory of dynamical stability of wave packets - Arkhipov, V.V. (Ye.A.Buketov Karaganda State University Publishing house, 2010)
In this article we show that a wave packet for massive particles can save pseudo stability, if it is composed with a discrete set of harmonics. This packet, after periodicity in a consequence of dispersion, is reconstructed at some smearing. Such behavior is denoted in this paper as dynamical stability and may be used as an illustration of a particle moving through physical vacuum, that is characterized by periodic annihilations with appropriate antiparticles and delivery of its momentum to the next identical particle.
Keywords: wave packet; comprising waves; periodicity; annihilations; dynamical stability